Anifrolumab, an Anti–Interferon‐α Receptor Monoclonal Antibody, in Moderate‐to‐Severe Systemic Lupus Erythematosus. Issue 2 (February 2017) - Furie, Richard; Khamashta, Munther; Merrill, Joan T.; Werth, Victoria P.; Kalunian, Kenneth; Brohawn, Philip; Illei, Gabor G.; Drappa, Jorn; Wang, Liangwei; Yoo, Stephen; ,
Abstract : Objective: To assess the efficacy and safety of anifrolumab, a type I interferon (IFN) receptor antagonist, in a phase IIb, randomized, double‐blind, placebo‐controlled study of adults with moderate‐to‐severe systemic lupus erythematosus (SLE). Methods: Patients (n = 305) were randomized to receive intravenous anifrolumab (300 mg or 1, 000 mg) or placebo, in addition to standard therapy, every 4 weeks for 48 weeks. Randomization was stratified by SLE Disease Activity Index 2000 score (<10 or ≥10), oral corticosteroid dosage (<10 or ≥10 mg/day), and type I IFN gene signature test status (high or low) based on a 4‐gene expression assay. The primary end point was the percentage of patients achieving an SLE Responder Index (SRI[4]) response at week 24 with sustained reduction of oral corticosteroids (<10 mg/day and less than or equal to the dose at week 1 from week 12 through 24). Other end points (including SRI[4], British Isles Lupus Assessment Group [BILAG]–based Composite Lupus Assessment [BICLA], modified SRI[6], and major clinical response) were assessed at week 52. The primary end point was analyzed in the modified intent‐to‐treat (ITT) population and type I IFN–high subpopulation. The study result was considered positive if the primary end point was met in either of the 2 study populations. The Type I error rate was controlled at 0.10 (2‐sided), within each of the 2 study populations for the primary end point analysis. Results: The primary end point was met by more patients treated with anifrolumab (34.3% of 99 for 300 mg and 28.8% of 104 for 1, 000 mg) than placebo (17.6% of 102) ( P = 0.014 for 300 mg and P = 0.063 for 1, 000 mg, versus placebo), with greater effect size in patients with a high IFN signature at baseline (13.2% in placebo‐treated patients versus 36.0% [ P = 0.004] and 28.2% [ P = 0.029]) in patients treated with anifrolumab 300 mg and 1, 000 mg, respectively. At week 52, patients treated with anifrolumab achieved greater responses in SRI(4) (40.2% versus 62.6% [ P < 0.001] and 53.8% [ P = 0.043] with placebo, anifrolumab 300 mg, and anifrolumab 1, 000 mg, respectively), BICLA (25.7% versus 53.5% [ P < 0.001] and 41.2% [ P = 0.018], respectively), modified SRI(6) (28.4% versus 49.5% [ P = 0.002] and 44.7% [ P = 0.015], respectively), major clinical response (BILAG 2004 C or better in all organ domains from week 24 through week 52) (6.9% versus 19.2% [ P = 0.012] and 17.3% [ P = 0.025], respectively), and several other global and organ‐specific end points. Herpes zoster was more frequent in the anifrolumab‐treated patients (2.0% with placebo treatment versus 5.1% and 9.5% with anifrolumab 300 mg and 1, 000 mg, respectively), as were cases reported as influenza (2.0% versus 6.1% and 7.6%, respectively), in the anifrolumab treatment groups. Incidence of serious adverse events was similar between groups (18.8% versus 16.2% and 17.1%, respectively). Conclusion: Anifrolumab substantially reduced disease activity compared with placebo across multiple clinical end points in the patients with moderate‐to‐severe SLE.